The emergence of the Ash'ari doctrine in the Islamic East - Resea. Shatha Ali Kazem (Journal of College of Education, 2024)
The Ash'ari school of thought was founded and it is considered one of the Islamic theological schools of thought whose intellectual products are followed by most of the Sunnis and the community. The founder of the Ash'ari school of thought is Abu Al-Hasan Al-Ash'ari. He spent most of his life in the school of isolation, but at the end of his life he left this school of thought and founded a new school named after him, and the Ash'aris are the owners of a new idea or an innovative school of thought. In fact, it is a new name for the doctrine of the Sunnis and the community. The real new thing in this doctrine is that it used the evidence of its Mu’tazila opponents to refute their opinions and arguments. This means that Al-Ash’ari left the Mu’tazila doctrine for political reasons, so ideas changed with the change in authority.
Keywords: doctrine, Ash'ari, Arab Levant, Mu'tazila.